Etiologic Spectrum of Optic Disc Edema in Mongolia: Clinical Insights from a Resource Limited Setting (Central Asian Journal of Medical Sciences, 2025)
Objective: Optic disc edema (ODE) is a critical clinical sign that often marks the initial manifestation of a vision- or life-threatening systemic disease, depending on its underlying etiology. This first Mongolian observational study defines the demographic characteristics, etiologies, and clinical features of ODE, assessing diagnostic reassessment as a challenge for multiple specialties. Methods: We conducted a 5-year retrospective–prospective observational study with reassessment to evaluate etiologies, clinical features, and visual outcomes. Results: Seventy patients (90 eyes) with optic disc edema were included in the analysis. Demyelinating optic neuritis (36.4%) predominated in younger females, ischemic cases (44.4%) in older patients, and infectious causes (26.9%, syphilis) in males. Inflammatory etiologies were mostly uveitis. Baseline vision was poor, with 20% presenting with profound impairment (Visual acuity (VA)≤20/400). Severe loss (